Intravenous leiomyomatosis - Mittal, Rita; Dhiman, Bishan; Sharma, Himani; Pal, Aleeza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Intravenous leiomyomatosis is a rare benign smooth muscle tumour arising from a venous wall or a uterine leiomyoma. This case highlights that intra-cardiac leiomyomatosis should be considered as a differential diagnosis in addition to extended cancer or thrombus, in female patients, diagnosed with a right sided cardiac mass extending from the IVC. To prevent pulmonary embolism or sudden death in patients with intra-cardiac extension, complete surgical resection is necessary. One stage surgical removal has been recommended for complete resection.